1993
DOI: 10.1063/1.858714
|View full text |Cite
|
Sign up to set email alerts
|

Wave formation in the gravity-driven low-Reynolds number flow of two liquid films down an inclined plane

Abstract: Wave formation in the gravity-driven low-Reynolds number flow of two liquid films down an inclined plane is studied by a linear stability analysis. Wavy motion can appear due to an instability of either the fluid–fluid interface or the fluid-air free surface. It is shown that the flow is always unstable and wavy motion can occur when the less viscous layer is in the region next to the wall for any Reynolds number and any finite interface and surface tensions. Stability can be achieved for the configuration wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 20 publications
5
47
0
3
Order By: Relevance
“…This result was extended to the case of arbitrary wavenumber in the Stokes flow limit, and in the absence of interfacial and surface tension, by Loewenherz and Lawrence [14]. Further analysis by Chen [15] allowed for surface tension and inertia and concluded that the clean two-layer flow is always unstable at any Reynolds number if the less viscous fluid is next to the wall. Jiang and Lin [16] showed that the unstable two-layered flow on a vertically inclined plate can be stabilised by oscillating the plate in its own plane.…”
Section: Introductionmentioning
confidence: 87%
“…This result was extended to the case of arbitrary wavenumber in the Stokes flow limit, and in the absence of interfacial and surface tension, by Loewenherz and Lawrence [14]. Further analysis by Chen [15] allowed for surface tension and inertia and concluded that the clean two-layer flow is always unstable at any Reynolds number if the less viscous fluid is next to the wall. Jiang and Lin [16] showed that the unstable two-layered flow on a vertically inclined plate can be stabilised by oscillating the plate in its own plane.…”
Section: Introductionmentioning
confidence: 87%
“…In view of its existence in Stokes flows (in the absence of inertia), this is referred to as interfacial inertialess instability. Following Kao [7], stability of multilayer free surface flows has been considered in a number of investigations [11,[13][14][15][16][17][18][19][20][21][22][23]. Loewenherz and Lawrence [11] have examined the effects of viscosity stratification on the linear stability of a two-layer flow with equal densities down an inclined substrate within the framework of Orr-Sommerfeld analysis, in the limit of Stokes flow and negligible surface tension both at the liquid-liquid interface and at the free surface.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the neutral stability is independent of the angle of inclination of the inclined substrate but the growth rate of instability is not. The study by Chen [14] has incorporated the inertial effects in the linear stability analysis and has explored the influence of surface tension at the free surface and the interfacial tension at the liquid-liquid interface. A configuration with less viscous fluid adjacent to the wall has been observed to be unstable for any Reynolds number and any finite surface tension and interfacial tension.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that two-layer flows in inclined or pressure-driven channels and single-layer free-surface flows down inclined planes, require fluid inertia for destabilisation, at least when the inclination to the horizontal is less than ninety degrees (see Chen 1995;Benjamin 1957;Yih 1963). However, in the case of two-layer free-surface flows, Kao (1968), Loewenherz & Lawrence (1989) and Chen (1993) showed that when the less viscous fluid is adjacent to the wall, then a long-wave instability can appear in the absence of inertia (zero Reynolds number); this instability has been termed inertialess instability. Chen (1993) argues that the instability arises from an interaction between the free surface and the interface, while an interpretation of the underlying mechanism has been given recently by Gao & Lu (2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of two-layer free-surface flows, Kao (1968), Loewenherz & Lawrence (1989) and Chen (1993) showed that when the less viscous fluid is adjacent to the wall, then a long-wave instability can appear in the absence of inertia (zero Reynolds number); this instability has been termed inertialess instability. Chen (1993) argues that the instability arises from an interaction between the free surface and the interface, while an interpretation of the underlying mechanism has been given recently by Gao & Lu (2008). An analogous linear stability study was undertaken by Li (1969), for Couette flow of three superposed fluids of different viscosities; it was shown that the flow can become unstable in the long-wavelength limit for certain values of the depth and viscosity ratio due to resonance between the interfaces, something that does not happen if the additional interface is not present.…”
Section: Introductionmentioning
confidence: 99%